2001
DOI: 10.1161/hh1301.093953
|View full text |Cite
|
Sign up to set email alerts
|

Number and Migratory Activity of Circulating Endothelial Progenitor Cells Inversely Correlate With Risk Factors for Coronary Artery Disease

Abstract: Abstract-Recent studies provide increasing evidence that postnatal neovascularization involves bone marrow-derived circulating endothelial progenitor cells (EPCs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

79
1,822
15
53

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 2,138 publications
(1,969 citation statements)
references
References 49 publications
79
1,822
15
53
Order By: Relevance
“…Numerous studies have reported inverse correlations of EPC numbers and migratory function with low‐density lipoprotein cholesterol 15, 19. The data we present in this study are the first to demonstrate a cell autonomous role for LXRs in the cholesterol‐mediated dysfunction of EPCs.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Numerous studies have reported inverse correlations of EPC numbers and migratory function with low‐density lipoprotein cholesterol 15, 19. The data we present in this study are the first to demonstrate a cell autonomous role for LXRs in the cholesterol‐mediated dysfunction of EPCs.…”
Section: Discussionsupporting
confidence: 62%
“…These changes in EPC differentiation and secretome were recapitulated when Lxr αβ −/− chow EPCs (but not WT chow EPCs) were treated with cholesterol in culture, suggesting that this was the component of the WD mediating this change. Interestingly, previous clinical studies of EPCs from patients with cardiovascular disease or diabetes mellitus provide evidence that EPCs may passively contribute to disease progression by reducing the migration, proliferation, or tube formation capacity of the cells 15, 18. However, herein we show that the loss of LXRs combined with an increase in EPC cholesterol content produces an EPC population that may actively contribute to disease progression by directly promoting monocyte adhesion to activated endothelial cells.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…The correlations noted are likely the result of previously reported relationships between endothelial function and EPC numbers, and function 35,36 along with the relationship between endothelial number and FMD. 37 All of these are altered in hypertension, 3,38,39 and in these alterations oxidative stress has a pivotal role. 40 Relationships between EPCs, FMD and HO-1 LA Calò et al in BS/GS patients.…”
Section: Discussionmentioning
confidence: 99%
“…One of the major concerns when envisioning autologous (progenitor/stem) cell therapy in cardiovascular medicine, is the presumed dysfunctional progenitor cell phenotype in older and diseased patients burdened with risk factors, as evidenced for early outgrowth EPCs of monocytic origin (also known as circulating angiogenic cells),9, 10, 11, 12 CD133 + /VEGFR2+ circulating EPCs,10, 13 colony‐forming‐unit EPCs (CFU‐Hill),13, 14 bone‐marrow–derived mononuclear cells (MNCs)15 and hematopoietic stem cells 11…”
Section: Introductionmentioning
confidence: 99%